Proofs

A proof is a series of claims that lead to a conclusion. Some proofs are conditional, which means that the claims can only be made under certain conditions. Click on a statement to see the proof

Truth Propagation Property 2
if the following are true:
  • a
  • b = a

then b


Transitive Property of Equality Variation 1
if the following are true:
  • a = c
  • b = c

then a = b


Transitive Property of Equality Variation 2
if the following are true:
  • a = b
  • a = c

then b = c


Transitive Property of Equality Variation 3
if the following are true:
  • a = b
  • b = c

then c = a


Transitive Property of Equality Variation 4
if the following are true:
  • a = b
  • c = a

then b = c


Transitive Property Application 1
if the following are true:
  • a = b
  • b = c
  • c = d

then a = d


Transitive Property Application 2
if the following are true:
  • a = b
  • a = c
  • b = d

then c = d


Propagated Transitive Property 3
if the following are true:
  • a = x
  • b = y
  • x = y

then a = b


Multiply by 0
0a = 0

Inverse Product Theorem
(1 / a) ⋅ a = 1

Reordering Terms Theorem
(ab) ⋅ c = (ca) ⋅ b

Multiply By 1 Theorem
(b / c) ⋅ c = b

Multiply by 1 3
if a1 = b, then a = b

Multiply Both Sides 2
if a = b / c, then ca = b

Double
if a + a = b, then a2 = b

Subtract Substitute 2 Vars
if the following are true:
  • a = b
  • c = d

then a - c = b - d


Multiply by 2
if a2 = b, then a = b ⋅ (1 / 2)

Double to Half
if a + a = b, then a = b ⋅ (1 / 2)

Rearrange Sum
if (a + b) + c = d, then (a + c) + b = d

Rearrange Sum 2
if (a + b) + c = d, then (b + a) + c = d

Simplify Rearrange Sum 6
if the following are true:
  • x = c + d
  • y = e + f

then ((a + b) + (c + d)) + (e + f) = ((a + b) + x) + y


Divide Each Side
if ab = c, then a = c / b

One Eighty 3
if (a + b) + b = 180, then a + (b2) = 180

Transitive
if x = (0 + (a2)) / 2, then x = a

Transitive 2
if x = ((b2) + (a2)) / 2, then x = b + a

Subtract Zero Example 2
if f = a - 0, then f = a

Transitive Subtract 3
if f = (a + b) - b, then f = a

Transitive Inequality
if the following are true:
  • a < b
  • c = a

then c < b


Subtract Substitute
if a = b, then x - a = x - b

Substitute 11
if the following are true:
  • a = b
  • f = c - a

then f = c - b


Subtract Both Sides 3
if a = b, then a - c = b - c

Subtract Move Over
if a - b = c, then a = c + b

Subtract to Zero 3
if a - b = 0, then a = b

Sum to Double
if c = a + a, then c = a2

Proportion Product
if a / b = c / d, then da = bc

Simplify3
((x4) ⋅ 2) - (22) = ((x4) ⋅ 2) - 4

Simplify4
((x4) ⋅ 2) - 4 = (x8) - 4

Distribute Subtract2
(ca) - (cb) = c ⋅ (a - b)

Additive Inverse 2
(a2) + (a ⋅ (-2)) = 0

Half Half One
((a1) / 2) + ((a1) / 2) = a

Multiply by One
(a ⋅ (1 / c)) ⋅ c = a

Substitute 12
if the following are true:
  • a = b
  • bc = d

then ac = d


Divide Numerators
if a / c = b / c, then a = b

Divide Numerators 2
if a / c = b / c, then b = a

Substitution 2
if the following are true:
  • a / b = c / d
  • a = w
  • b = x
  • d = z

then w / x = c / z


Reorder Terms
((ab) ⋅ c) ⋅ d = ((bd) ⋅ a) ⋅ c

Reduction Property
((a / b) ⋅ c) ⋅ b = ac

Cross Multiply Theorem
if a / b = c / d, then ad = bc

Multiply by One 2
if the following are true:
  • ab = c
  • d = b

then ad = c


Divide by 1
if a = 1, then b / a = b

Divide by 2
(a2) / (b2) = a / b

Algebra
if the following are true:
  • a = (b + c) + d
  • b = x + y

then a = ((x + y) + c) + d


Algebra2
if the following are true:
  • a = ((b + c) + d) + e
  • b = x + y

then a = (((x + y) + c) + d) + e


Distribute 4
(a2) + (a2) = a4

Angle180 90
if 180 = a + 90, then a = 90

Divide 180 by 2 2
if a2 = 180, then a = 90

One Eighty 4
if a + a = 180, then a = 90

Simplify 4
(((-1) ⋅ 3) ⋅ x) + ((3x) + 20) = 20

Simplify 5
(((-1) ⋅ 3) ⋅ x) + (4x) = x

Simplify If
if (3x) + 20 = 4x, then 20 = x

Reorder Terms 3
if ((a + b) + c) + e = ((a + b) + g) + h, then ((a + b) + c) + e = ((a + g) + b) + h

Reorder Terms 4
if (a + b) + c = 180, then a + c = 180 + (b ⋅ (-1))

Reorder Terms 5
if the following are true:
  • a = b + c
  • c = d

then b + d = a


Transitive With Four
if the following are true:
  • a = b
  • b = d
  • a = c

then d = c


Reorder Terms 6
if ((a + b) + a) + b = 360, then a + b = 180

Reduce Addition
if ((a + a) + a) + a = 360, then a = 90

Reduce Addition 2
if a + a = 90, then a = 45

Three Angles
if 60 + (a2) = 180, then a = 60

Algebra 3
if the following are true:
  • x = 12
  • d = (x2) + 1

then d = 25


Algebra 4
if the following are true:
  • x = 12
  • d = x + 13

then d = 25


Additive Identity Variation 2
if the following are true:
  • a = 0
  • b = e

then a + b = e


Algebra Example
if the following are true:
  • y = (a + b) / 2
  • a = 0
  • b = e

then y = e / 2


Subtraction Example
if x = a - a, then x = 0

Zero Numerator Property Example
if the following are true:
  • x = 0 / y
  • not (y = 0)

then x = 0


Subtract Zero Example 3
if the following are true:
  • b = 0
  • a = 0

then b - a = 0


Algebra 5
if a + b = 180 - 90, then a + b = 90

Compute 1
if a = 90 - 67, then a = 23

Compute 2
if a = 90 - 23, then a = 67

Algebra 6
(a / b) ⋅ d = (d / b) ⋅ a

Algebra 7
(ax) / x = a

Algebra Divide
if a / b = c / d, then d / b = c / a

Algebra One
if the following are true:
  • a = 1
  • aa = b

then 1 = b


Substitution 15
if a = b, then aa = bb

Algebra Square Sum
if the following are true:
  • x = (aa) + (bb)
  • m = a
  • n = b

then x = (nn) + (mm)


Algebra Substitution
if the following are true:
  • aa = (bb) + (cc)
  • a = x
  • b = y

then xx = (yy) + (cc)


Swap Terms 2 and 3
((ab) ⋅ c) ⋅ d = ((ac) ⋅ b) ⋅ d

Algebra 8
(s / 2) ⋅ (s / 2) = (ss) / 4

Algebra 9
if a = b + c, then a - b = c

Algebra 10 Help
a + (b ⋅ ((-1) / c)) = a - (b / c)

Algebra 10
(ss) - ((ss) / 4) = (3 / 4) ⋅ (ss)

Algebra 11
if the following are true:
  • a = b / c
  • d = b
  • c = e

then a = d / e


Algebra 11a
if the following are true:
  • a = b / c
  • b = d
  • c = e

then a = d / e


Substitution 16
if a = bc, then aa = ((bc) ⋅ b) ⋅ c

Square Product Example
(ss) ⋅ (1 / 4) = (s / 2) ⋅ (s / 2)

Square Root Example
square root of ((ss) ⋅ (1 / 4)) = s / 2

Shuffle Example
(3 / 4) ⋅ (ss) = 3 ⋅ ((ss) ⋅ (1 / 4))

Square Root Example 2
square root of ((3 / 4) ⋅ (ss)) = (square root of 3) ⋅ (s / 2)

Square Root 2
if a = bb, then square root of a = b

Algebra 17
s ⋅ (1 / s) = 1

Algebra 17b
(s / 2) / s = 1 / 2


1 2